If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -2 = 4f Reorder the terms: -2 + 3f = 4f Solving -2 + 3f = 4f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-4f' to each side of the equation. -2 + 3f + -4f = 4f + -4f Combine like terms: 3f + -4f = -1f -2 + -1f = 4f + -4f Combine like terms: 4f + -4f = 0 -2 + -1f = 0 Add '2' to each side of the equation. -2 + 2 + -1f = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1f = 0 + 2 -1f = 0 + 2 Combine like terms: 0 + 2 = 2 -1f = 2 Divide each side by '-1'. f = -2 Simplifying f = -2
| 45(2)=45+6h | | 4K=45-k | | 1.8(-10)+32= | | 4K=45-4k | | 1.2(z-2)=2-x | | 6x(2x-7)=x | | 6y+5=39 | | 4z/(-16)=(-16) | | -17-x=-35 | | 5m+11(12+7m)=5m-8(-6m-2) | | s^2-19s=-88 | | 3m/5-3/20 | | -4y+x+z=6 | | r(b-3)+t(b-3)= | | 18=15+a | | 29=13+b | | 4(b-2)=2(5-6) | | 0.02q+2.1r=3.16-.2r | | -2(x-4)=3x+7 | | 16x^2-10x^2+8x=0 | | 18-m=16 | | 5p-6p=1 | | 5r+4s= | | 10(6x-2)=+4(12x+6) | | s^2-19s+88=0 | | (2x+5)+(5x-7)=18 | | 1/4x=1/4x | | 6=-5a+4a | | 31-4(2x+11)=19 | | 3+3x+3=x-1 | | .74(x-12)=12 | | b-4=-4-4b |